SEGMENTASI KONSUMEN PRODUK ELEKTRONIK HEMAT ENERGI LISTRIK (STUDI PADA KELOMPOK KONSUMEN RUMAH TANGGA DI KOTA MALANG) - Etsa Astridya Setiyati; Lidia Halim (Akademi Akuntansi YKPN Yogyakarta, 2015)
Electricity consumption needs to be managed well considering the demand for electricity is high, especially in household sector. Energy-saving electronic products is part of the green products which are offered to consumers in the attempt to create environmental sustainability. The study aims to identify the segmentation of green consumers for electronic products in Malang based on demographic variables (gender, age, education level and income level), psychographics (lifestyle, personality, and social class), and behavior (attitude toward the product and the use of the product). K-means cluster is employed to analyze data and to identify this segmentation. The results consist cluster 1 (curious consumers), cluster 2 (energy-saving-oriented consumers), and cluster 3 (selfish consumers). Implications for developing marketing strategy for each customer clusters are suggested. Keywords: sustainable marketing, green consumers, electronics, segmentation